Elastic Stable Intramedullary Nailing for Pediatric Humeral Shaft Fractures Under Ultrasonographic Guidance: A Retrospective Study - Li, Jun; Wu, Jun; Zhang, Yuan; Gou, Pan; Li, Xiang; Shi, Mingyan; Zhang, Man; Wang, Peikang; Liu, Xing (Frontiers in Pediatrics, 2022)
Objective: Fixation with an elastic stable intramedullary nail (ESIN) is a widely used technique for the treatment of humeral shaft fractures. Ultrasonography (US) is used as an auxiliary tool and alternative to radiography during surgery to reduce radiation damage, but whether it is effective in pediatric patients is not known. In this study we evaluated the utility of US in the treatment of pediatric humeral shaft fractures by closed reduction and fixation with an ESIN. Methods: Children who were admitted to our hospital with humeral shaft fractures were retrospectively examined from January 2016 to March 2019. The patients were divided into 2 groups, US (treated by US-guided closed reduction and ESIN fixation) and non-US (treated with the same technique but with intraoperative radiography instead of US). The postoperative functional recovery of the 2 groups was compared. Results: The study population comprised 28 boys and 17 girls (age range: 4-16 years) with humeral shaft fractures. US significantly reduced radiation exposure during the operation (P=0.008), and intraoperative US facilitated the detection of nerve and vascular injury and aided surgical planning. There was no difference between the 2 groups in postoperative recovery based on the Constant–Murley shoulder score (CMS). Conclusions: These results demonstrate that US-guided closed reduction and ESIN fixation for humeral shaft fractures can limit radiation exposure and help doctors to determine the optimal surgical strategy to avoid radial nerve injury.